Examining the Roles of Education Civil Society Organizations in Supporting Tertiary Enrollment in Indonesia: A Case Study of the Suryanara Foundation - Lavinia DW Araminta; Wimba W Dinutanayo (UIII Press, 2025)
This study addresses the low tertiary educational attainment in Indonesia despite the critical role of higher education in societal development. The research aims to assess the contribution of an Indonesian Civil Society Organization (CSO), specifically the Suryanara Foundation, through its mentoring program, Adik Asuh Suryanara, on tertiary enrollment. The study utilizes a case study research design focusing on the organized mentoring program, examining both objective outcomes (tertiary enrollment achievements) and subjective outcomes (participant perceptions). Data collection involved document analysis and a survey conducted among program participants. Results indicate that a significant majority of scholarship awardees successfully enrolled in universities, primarily in state institutions and highly-ranked universities across various disciplines. This achievement is coupled with the perceived personal development of the program participants in terms of the creation of a college-going culture, instrumental and communicative learning, role modeling by mentors, and a sense of community establishment among participants. The study suggests the essential roles of the Suryanara Foundation as an advocate for distributive justice, an agent of empowerment, and a collaborator in supporting tertiary enrollment in Indonesia. By evaluating the effectiveness of the CSO-led mentoring program, this research contributes to the CSO literature towards strengthening the roles of CSOs in enhancing tertiary education access and quality.